Resistance to antibiotic drugs - Zoonotic and Emerging Diseases Research Team (Zoonotic and Emerging Diseases Research Team, 2019)
Learn about how you can play your part in preventing antimicrobial resistance. This video was created primarily for and East African audience, and was funded by a UK BBSRC/GCRF Public Engagement grant (https://bbsrc.ukri.org/innovation/max...) implemented by Laura Falzon and Katie Hamilton who are part of the Zoonotic and Emerging Diseases Group, which is based jointly between the University of Liverpool (UK) and the International Livestock Research Institute (Kenya). The work is also supported by the CGIAR Agriculture for Nutrition and Health Program.